Influência da maceração carbônica e da irradiação ultravioleta-C nos níveis de trans-resveratrol em vinhos tinto e branco - Bertagnolli, Silvana Maria Michelin (2004)
The objective of this work is to determine the trans-resveratrol, in red and white wines which are produced by two different techniques of vinification: carbonic maceration and ultra-violet irradiation C (UV-C), using Cabernet Sauvignon and Trebbiano grapes. The evaluation of wine acceptance was determined by sensorial analysis. Furthermore, some physicchemical parameters were evaluated, such as the determination of alcohol content by ebuliometry, total acidity by titulometry measurement, volatile acidity by titulometry with steam drag, reducing sugar by Lane & Eynon method, and dry stratum by evaporation at 100º C, until constant weight. Total polyphenol and antocyanines were analyzed on red wines, while only the total polyphenol was analyzed on white wines. Color, taste, and smell were the sensorial parameters analyzed by means of Hedonic Scale with five points by non-trained wine tasters which were chosen randomly. Transresveratrol analysis was accomplished by High Performance Liquid Chromatography (HPLC). In relation to alcoholic levels, and to dry stratum, the results have shown that there weren’t significant differences among different treatments on red wines, as well as on white wines. In red wines, the only significant difference in relation to total and volatile acidity has occurred in the wine, which was submitted to carbon maceration, while in white wines it was not observed any difference between treatments. For reducing sugar contents, there were differences between red wines, on those which the ultraviolet irradiation UV-C, and carbon maceration were used together; and between white wines, on those which grapes were only irradiated. There was a less significant difference in relation to total polyphenol on treatment with wines of irradiated grapes, and with carbon maceration, and of total antocyanines the lowest value was also found on red wines of this treatment. Total polyphenol values of white wines have shown significant difference between the controlled treatment, and the one, which has used only grapes of carbon maceration. Most of wine tasters enjoyed the color of red wines in any treatment. However, the same behavior was not observed when smell and taste were evaluated, because they have presented quite different attributes between treatments. The wine tasters have enjoyed the color of white wines on control, those from of carbonic maceration only, and those from whith irradiation and carbon maceration were used together, but they did not like the wines which grapes were only irradiated. In relation to taste, the wine tasters have enjoyed wines of carbon maceration more. Wines only irradiated or only with carbon maceration have received the best grades in relation to smell. Independently of the applied technique, the evolution of the transresveratrol content, in red wines, was similar between treatments, achieving the final main fermentation at the average concentration of 15 mg/L, and at the end of storage period, of 1,5 mg/L. On white wines, the behavior was similar to red wines, with values, which did not change during the different phases of vinification, probably due to the fact that fermentation on white wines does not occur with the skin.